Constricted migration is associated with stable 3D genome structure differences in cancer cells. (15th August 2022) - Golloshi, Rosela; Playter, Christopher; Freeman, Trevor F; Das, Priyojit; Raines, Thomas Isaac; Garretson, Joshua H; Thurston, Delaney; McCord, Rachel Patton
Abstract: To spread from a localized tumor, metastatic cancer cells must squeeze through constrictions that cause major nuclear deformations. Since chromosome structure affects nucleus stiffness, gene regulation, and DNA repair, here, we investigate the relationship between 3D genome structure and constricted migration in cancer cells. Using melanoma (A375) cells, we identify phenotypic differences in cells that have undergone multiple rounds of constricted migration. These cells display a stably higher migration efficiency, elongated morphology, and differences in the distribution of Lamin A/C and heterochromatin. Hi‐C experiments reveal differences in chromosome spatial compartmentalization specific to cells that have passed through constrictions and related alterations in expression of genes associated with migration and metastasis. Certain features of the 3D genome structure changes, such as a loss of B compartment interaction strength, are consistently observed after constricted migration in clonal populations of A375 cells and in MDA‐MB‐231 breast cancer cells. Our observations suggest that consistent types of chromosome structure changes are induced or selected by passage through constrictions and that these may epigenetically encode stable differences in gene expression and cellular migration phenotype. Synopsis: Repeated migration of cancer cells through constrictions leads to a population of cells with stably altered cellular, nuclear, and migratory phenotypes. These cells have alterations in 3D chromosome organization, including reorganization of chromatin compartments. Hi‐C reveals chromosome alterations in cancer cells that have migrated numerous times through constrictions. Some chromosome spatial compartment switches are associated with alterations in gene expression. Contact loss within heterochromatic regions after constricted migration is a shared feature across different cell clones. Sequentially constricted cells show a spatial redistribution of Lamin A/C and heterochromatin foci. Abstract : Repeated migration of cancer cells through constrictions leads to a population of cells with stably altered cellular, nuclear, and migratory phenotypes. These cells have alterations in 3D chromosome organization, including reorganization of chromatin compartments.